2016
DOI: 10.1016/j.scp.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and chemometric strategies for the development of Green Analytical Chemistry (GAC) spectroscopic methods for the determination of organic pollutants in natural waters

Abstract: The development of Green Analytical Chemistry (GAC) methods is one of the most active areas of Green Chemistry. Especially relevant are GAC methods devoted to the detection and quantification of environmental pollutants, because they should not pollute the environment more than the analyte to be determined. While considerable attention has been paid to develop environmentally friendly alternatives for the first stage of the global analytical process (e.g., sample preparation techniques), relatively fewer works… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…The development and evolution of the scientific literature related to the assessment of green analytical methods is growing annually, due to the need to advance new practices that comply with ecological requirements [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. The emergence of many greenness assessment studies has gained attention as they are intended to reduce waste production, energy consumption, and cost and generate eco-friendly methods.…”
Section: Resultsmentioning
confidence: 99%
“…The development and evolution of the scientific literature related to the assessment of green analytical methods is growing annually, due to the need to advance new practices that comply with ecological requirements [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. The emergence of many greenness assessment studies has gained attention as they are intended to reduce waste production, energy consumption, and cost and generate eco-friendly methods.…”
Section: Resultsmentioning
confidence: 99%
“…A useful way to solve the spectral overlapping and to use all the information contained in the spectrum of complex matrices is the multivariate calibration methods [ 28 ], extensively applied to NIR-IR [ 29 , 30 , 31 , 32 , 33 ]. Several works demonstrated that NIR-IR techniques can be applied as a tool for quantitative multivariate analysis, especially with the combination of separation and preconcentration methods for organic compounds [ 34 , 35 ], and metal ions [ 36 , 37 , 38 ], where some of them use NIR-IR followed by MID-IR and Raman [ 39 ]. Even though it’s a drawback, the popularity of NIR is related to the good band assignments, improvements in instrumentation, and progress in statistical and mathematical methods [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…This analytical stage is, perhaps, the one that has received more attention in developing greener approaches for the determination of environmental pollutants, and numerous reviews and articles have been published on the subject [2]. This fact is not surprising since sample pretreatment is considered the most polluting step.…”
Section: Introductionmentioning
confidence: 99%